2016
DOI: 10.1080/10799893.2016.1193522
|View full text |Cite
|
Sign up to set email alerts
|

The role of α1-adrenergic receptors in regulating metabolism: increased glucose tolerance, leptin secretion and lipid oxidation

Abstract: The role of α-adrenergic receptors (α-ARs) and their subtypes in metabolism is not well known. Most previous studies were performed before the advent of transgenic mouse models and utilized transformed cell lines and poorly selective antagonists. We have now studied the metabolic regulation of the α- and α-AR subtypes in vivo using knock-out (KO) and transgenic mice that express a constitutively active mutant (CAM) form of the receptor, assessing subtype-selective functions. CAM mice increased glucose toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 72 publications
1
27
0
Order By: Relevance
“…Catecholamines and inflammatory cytokines are important regulators of myoblast function and muscle growth (Barnes et al, 2017;Merrick et al, 2017). Adrenergic regulation is primarily facilitated by β2 receptors which are the most highly expressed isoform in skeletal muscle, although β1 receptors and to a lesser extent β3 and α 1D receptors are also present (Kim et al, 1991;Shi et al, 2017). Growth studies in animals have led to the use of isoform-specific β adrenergic agonists as growth-promoting feed supplements for finishing livestock, which can increase meat yield of feedlot cattle by up to 40% (Johnson et al, 2014).…”
Section: Adrenergic and Inflammatory Regulation Of Muscle Growthmentioning
confidence: 99%
“…Catecholamines and inflammatory cytokines are important regulators of myoblast function and muscle growth (Barnes et al, 2017;Merrick et al, 2017). Adrenergic regulation is primarily facilitated by β2 receptors which are the most highly expressed isoform in skeletal muscle, although β1 receptors and to a lesser extent β3 and α 1D receptors are also present (Kim et al, 1991;Shi et al, 2017). Growth studies in animals have led to the use of isoform-specific β adrenergic agonists as growth-promoting feed supplements for finishing livestock, which can increase meat yield of feedlot cattle by up to 40% (Johnson et al, 2014).…”
Section: Adrenergic and Inflammatory Regulation Of Muscle Growthmentioning
confidence: 99%
“…Thus, the impact that adrenergic stimulation has on a specific tissue is a function of the specific receptor type or types that it expresses. In skeletal muscle, β2 adrenergic receptors are the most highly-expressed isoform, but β1 receptors and to a lesser extent β3 and α 1D receptors are also present [7, 8]. Growth studies in animals [9] have led to the development of isoform-specific β adrenergic growth promoters that are used as feed additives in the livestock industry to increase meat yield per animal [10].…”
Section: Introductionmentioning
confidence: 99%
“…A few early studies suggested that α 1 -AR stimulation inhibits memory functions in monkeys (Arnsten and Jentsch, 1997;Mao et al, 1999) or in chickens (Gibbs and Summers, 2001) but used very low replicates, very high concentrations of ligands rendering them non-selective or attributed to species variation. Ross et al, 2003;Rorabaugh et al, 2005;Gupta et al, 2009;Shi et al, 2016Shi et al, , 2017 However, as will be discussed, most of the recent studies indicate that α 1 -AR stimulation increases various types of memory in both formation and storage.…”
Section: General Cognitionmentioning
confidence: 99%
“…α 1 -AR Stimulation Increases Glucose Tolerance α 1 -AR stimulation is known to increase glucose uptake in the heart or in primary myocytes (Doenst and Taegtmeyer, 1999;Egert et al, 1999;Shi et al, 2016Shi et al, , 2017Sato et al, 2018;Papay and Perez, 2020). The systemically expressing CAM α 1A but not the CAM α 1B -AR mice increased glucose uptake into the heart and only the α 1A -AR KO mice displayed decreased glucose uptake into the heart (Shi et al, 2017). In corroboration, the α 1A -selective agonist, A61603 increased glucose uptake into primary cardiomyocytes or human α 1A -AR transfected Chinese hamster ovary (CHO) cells (Sato et al, 2018).…”
Section: Metabolismmentioning
confidence: 99%